An Enforcing Resilience of Steep-slope Citrus Orchards against Slope Failure Caused by Torrential Rain - Tomoki Izumi; Naoyuki Yamashita; Noriyuki Kobayashi (Journal of Sustainable Development of Energy, Water and Environment Systems, 2025)

(untitled)
In Japan, citrus orchards have traditionally been located on steep slopes because of their favourable growing conditions. However, the unexpected torrential rain that hit western Japan in 2018 caused numerous slope failures in these steep-slope citrus orchards. This study aims to investigate a method to enforce the resilience of steep-slope citrus orchards against torrential rain-induced slope failures by changing the surface soil permeability in such orchards. Laboratory-scale rainfall infiltration experiments were conducted using soil tanks with different surface soil permeabilities by mixing clay. The results demonstrated that the higher the clay mixing ratio, the more rainfall infiltration was suppressed, thereby reducing the slope safety factor decrease. Therefore, it can be concluded that this method is effective for slope stability. However, achieving optimal permeability to stabilise the slope and provide the required water remains a challenge for the future, as it is necessary to provide the water needed for citrus cultivation.